2021
DOI: 10.1080/03036758.2020.1850481
|View full text |Cite
|
Sign up to set email alerts
|

Conservation pest control with new technologies: public perceptions

Abstract: New genetic tools can potentially mitigate the decline of biodiversity. Democratisation of science mandates public opinion be considered while new technologies are in development. We conducted eleven focus groups in New Zealand to explore three questions about novel technologies (gene drive and two others for comparison of pest control tools): (1) what are the risks/benefits? (2) how do they compare to current methods? and (3) who should be represented on a panel that evaluates the tools and what factors shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Third, in line with the theories of cognitive heuristics, social schema, and planned behavior (Ajzen & Fishbein, 2018;Fiske & Taylor, 1991;Gigerenzer & Gaissmaier, 2011;MacDonald et al, 2022;Scheufele & Lewenstein, 2005;Tversky & Kahneman, 1973;1974), our study showed that people tend to rely heavily on predisposition factors, which were developed and formed during their socialization processes, to guide and form their opinions about new biotechnological issues about which they have little information and knowledge. Future research should continue to examine the importance of predisposition variables.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Third, in line with the theories of cognitive heuristics, social schema, and planned behavior (Ajzen & Fishbein, 2018;Fiske & Taylor, 1991;Gigerenzer & Gaissmaier, 2011;MacDonald et al, 2022;Scheufele & Lewenstein, 2005;Tversky & Kahneman, 1973;1974), our study showed that people tend to rely heavily on predisposition factors, which were developed and formed during their socialization processes, to guide and form their opinions about new biotechnological issues about which they have little information and knowledge. Future research should continue to examine the importance of predisposition variables.…”
Section: Conclusion and Discussionsupporting
confidence: 80%
“…Planned behavior theorists premise that preexisting attitudes influence people's intentions and behaviors (Ajzen, 1991;Ajzen & Fishbein, 2018;Madden et al, 1992), showing that people's supporting or opposing actions are based on previously established attitudinal structures (Ajzen, 1991;Kim et al, 2014). Using the theory of planned behavior, MacDonald et al (2022) found that general attitudes toward new technology such as perceptions of harm/benefit and safety/risk are significant predictors of support for gene drive compared to other gene drive beliefs. Other researchers have also shown empirical associations between individuals' benefit-risk assessment and their acceptance of new biotechnology.…”
Section: Literature Review and Theoretical Expectationmentioning
confidence: 99%
See 1 more Smart Citation
“…The merits and concerns raised by these California residents are quite similar to those found in other survey, interview, and focus group studies. Other studies of communities or publics consistently discuss hopes that GE and gene drive will provide effective, safe, and economical solutions to the threat of vector-borne diseases ( Marshall et al, 2010 ; Hudson et al, 2019 ; Jones et al, 2019 ; Hartley et al, 2021 ; MacDonald et al, 2021 ). Likewise, these studies have recorded common concerns related to environmental impact, off-target impacts, human health risks, and general wariness of GE technologies.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, public engagement often takes the form of surveys and public opinion polls conducted to establish political will and influence policy debates, as well as inform more democratic scientific processes. ( Pew Initiative on Food Biotechnology, 2004 ; Marshall et al, 2010 ; Ernst et al, 2015 ; Glenza 2016 ; Hudson et al, 2019 ; Jones et al, 2019 ; MacDonald et al, 2020a ; MacDonald et al, 2020b ; MacDonald et al, 2021 ; Schairer et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%